We make the road by walking: a year-long quest for spiritual formation, reorientation, and activation - McLaren, Brian D. (Jericho Books, 2014)
These "fifty-two (plus a few) weekly readings can each be read aloud in 10-12 minutes, and offer a simple curriculum of insightful reflections and transformative practices. Organized around the traditional church year, these readings give an overview of the whole Bible and guide an individual or a group of friends through a year of rich study, interactive learning, and personal growth"--Dust jacket flap